Byzantine religious culture
1 online resource (xxxiv, 473 pages, [14] pages of plates)
Keywords: Alice-Mary Talbot has profoundly influenced Byzantine Studies in America and Europe, focusing her scholarship upon the social context of Byzantine religious practices. As Director of Byzantine Studies at Dumbarton Oaks and as editor of Dumbarton Oaks Papers, she touched the professional lives of senior and junior Byzantinists alike. This collection of twenty-five articles from scholars associated with her at various stages in her career compasses such varied disciplines as art history, social history, literature, epigraphy, numismatics and sigillography; contributions are grouped in three related sections: “Women,” “Icons and Images,” and finally “Texts, Practices, Spaces.” Illustrated with both b/w and color images, the volume is at once a varied and a coherent tribute to this extraordinary scholar. Contributors are Alexander Alexakis, Simon Bendall, Annemarie Weyl Carr, John Duffy, Stephanos Efthymiadis, Elizabeth A. Fisher, Jaroslav Folda, Sharon E. J. Gerstel, Michael Grünbart, Susan Ashbrook Harvey, Angela Constantinides Hero, Michel Kaplan, Paul Magdalino, Henry Maguire, Maria Mavroudi, Stamatina McGrath, Cécile Morrisson, John Nesbitt, Arietta Papaconstantinou, Stratis Papaioannou, Manolis Patedakis, Brigitte Pitarakis, Claudia Rapp, Nancy Patterson Ševčenko, Brooke Shilling, Paul Stephenson and Denis Sullivan.